Vanishing girls ebook - Oliver, Lauren (2015)
New York Times bestselling author Lauren Oliver delivers a raw and heart-pounding story, perfect for fans of E. Lockhart's We Were Liars or Gillian Flynn's Sharp Objects. Dara and Nick used to be inseparable, but that was before the accident that left Dara's beautiful face scarred and the two sisters totally estranged. When Dara vanishes on her birthday, Nick thinks Dara is just playing around. But another girl, nine-year-old Madeline Snow, has vanished, too, and Nick becomes increasingly convinced that the two disappearances are linked. Now, Nick has to find her sister, before it's too late. In this edgy and compelling novel, Lauren Oliver creates a world of intrigue, loss, and suspicion as two sisters search to find themselves, and each other.